The Conventions of Detective Fiction, or Why We Like Detective Novels: Hercule Poirot’s Christmas - Matković, Sanja (Anafora, 2023)
Detective fiction has been immensely popular among readers for decades. This paper answers the questions of who the readers of this genre are and what makes detective stories so attractive for them. The first part of the paper discusses why the so-called contemplatives are especially fond of detective fiction, which is often read as escapist literature, as well as why detective fiction is especially popular in Anglo-Saxon countries. In the second part of the paper, Agatha Christie’s novel Hercule Poirot’s Christmas is used as an example of organized structure and established conventions of detective fiction that make the genre appealing, which includes the setting, characterization, crime, detective, and restored order, i.e. a happy ending.